DIGITAL TECHNOLOGIES IN START-UP MANAGEMENT - Аверкина, Марина; Стасюк, Тетяна (SWorldJournal, 2024)
In the modern world, digital technologies are an integral part of the economy and have a significant impact on businesses of all sizes. The possibilities of using digital technologies in startups and their impact on business are examined in the article.